Pengaruh Periode Pengendalian Gulma Terhadap Komponen Hasil 3 Varietas Kedelai (Glycine Max (L) Merril) Berbeda Ukuran - Abdul Karim Kilkoda (Universitas Bangka Belitung, 2017)
This research conducted in research farm, Faculty of Agriculture, Ciparanje, Jatinangor from October 2014 to January 2015. This research aimed to verify the competition ability on plant growth of soybean varieties due to the presence of weeds with weeding frequency. The experiment was arranged in factorial randomized block design with three replications. The first factor was soybean variety and the second factor was weed competition period. The result of this research showed that seed size from each variety of observation time 4 WAP (weeks after planting) to 10 WAP not significantly different. Each treatment on weed control in 4 WAP also not significantly different. Next observation (6, 8 and 10 WAP) showed that there were significant differences in competition point. Observation in 6 WAP showed that G6 was bigger than G5. It means that soybean was able competed with weed. Treatment G7 and G8 were higher because right time control period of weed was the best time as a plant critical period where plant was sensitive to competition getting the necessary growth factors for plant growth and yield.